KEPEMIMPINAN VISIONER DALAM MENINGKATKAN MUTU PENDIDIKAN DI UNIVERSITAS ISLAM NEGERI IMAM BONJOL PADANG - -, Bustari (UIN Imam Bonjol Padang, 2019)
This study aims to determine 1) Policies taken by the leaders of Imam Bonjol Padang Islamic State University (UIN IB) in achieving the vision, mission and goals of the campus; and 2) Leaders' efforts in realizing visionary leadership for the advancement of UIN IB Padang. This research uses field research methods with qualitative descriptive analysis techniques. The collected data is then analyzed using the inductive approach. The results of this study indicate 1) The leadership of UIN IB Padang has conceptualized the campus vision to be more focused, focused, and oriented towards future challenges. In addition, in completing every program the leadership of UIN IB always has principles on the 4 principles of UIN IB values, which are: faithful, knowledgeable, moral and cultured; 2) The Chancellor of UIN IB Padang always fosters good relations between lecturers, employees and students, as well as to stakeholders. Furthermore, the Chancellor of UIN IB provides support so that all components of tertiary institutions can optimally improve performance, and always support the creativity of students, lecturers and employees. In addition, the Chancellor of UIN IB Padang always provides information to all campus leadership units to become a superior campus in Islamic scholarship in ASEAN in 2037. From some of the findings above, it can be concluded that the visionary leadership at UIN IB Padang has been optimally implemented.